Oral Contraceptives Modulate the Relationship Between Resting Brain Activity, Amygdala Connectivity and Emotion Recognition – A Resting State fMRI Study - Menting-Henry, Shanice; Hidalgo-Lopez, Esmeralda; Aichhorn, Markus; Kronbichler, Martin; Kerschbaum, Hubert; Pletzer, Belinda (Frontiers in Behavioral Neuroscience, 2022)
Recent research into the effects of hormonal contraceptives on emotion processing and brain function suggests that hormonal contraceptive users show (a) reduced accuracy in recognizing emotions compared to naturally cycling women, and (b) alterations in amygdala volume and connectivity at rest. To date, these observations have not been linked, although the amygdala has certainly been identified as core region activated during emotion recognition. To assess, whether volume, oscillatory activity and connectivity of emotion-related brain areas at rest are predictive of participant’s ability to recognize facial emotional expressions, 72 participants (20 men, 20 naturally cycling women, 16 users of androgenic contraceptives, 16 users of anti-androgenic contraceptives) completed a brain structural and resting state fMRI scan, as well as an emotion recognition task. Our results showed that resting brain characteristics did not mediate oral contraceptive effects on emotion recognition performance. However, sex and oral contraceptive use emerged as a moderator of brain-behavior associations. Sex differences did emerge in the prediction of emotion recognition performance by the left amygdala amplitude of low frequency oscillations (ALFF) for anger, as well as left and right amygdala connectivity for fear. Anti-androgenic oral contraceptive users (OC) users stood out in that they showed strong brain-behavior associations, usually in the opposite direction as naturally cycling women, while androgenic OC-users showed a pattern similar to, but weaker, than naturally cycling women. This result suggests that amygdala ALFF and connectivity have predictive values for facial emotion recognition. The importance of the different connections depends heavily on sex hormones and oral contraceptive use.